(untitled) (JURNAL ENFIT : Entomologi dan Fitopatologi, 2023)
One part of the study of insects associated in chrysanthemum plants is biomonitoring. Biomonitoring has a goal to use living organisms as a parameter in monitoring the effect on an agricultural ecosystem. The purpose of this study was to determine the associated insects on chrysanthemum plants in Kakaskasen II Village, North Tomohon District. The research was conducted using purposive sampling methods, the treatment was carried out in the vegetative phase and the generatif phase. Each treatment on the Chrysanthemum Plant was sampled 5 points diagonally for the Pitfall Trap and 4 points for the Yellow Trap. Then observations were made 3 times with time intervals every 3 days. Furthermore, the captured insects are brought to the laboratory of the Department of Pests and Plant Diseases, Sam Ratulangi University, Manado for identification. The results of the study found associated insects on chrysanthemum plants in Kakaskasen II Village, North Tomohon District, namely the Pitfall Trap 13 types of insects, namely the Order Coleoptera, Family Hydraenidae, Scarabaeidae, Staphylinidae, Tenebrionidae, Lampyridae, Carabidae, Scolytidae, Order Dermaptera, Family Forficulidae, Order Collembola Family Hypogastruridae and Isotomidae, Order Orthoptera Family Acrididae, Order Hymenoptera Family Formicidae and Order Hemiptera Family Cydnidae. For the Yellow Sticky Trap, it was found that there were 2 types of insects, namely the Order Coleoptera, Family Coccinelidae and Order Diptera, Family Tephritidae. From the results of the study, it can be concluded that the insects associated with chrysanthemum plants are 7 orders of 15 families consisting of insects and pests of 3 orders of 3 families, natural enemies totaling 3 orders and 10 families, and decomposers totaling 1 order 2 families.